Analysis of the Determinants of the Number of Child Workers in Indonesia for the Period 2018–2024 - Meta Adityas Savitri; Hardiani Hardiani; Dwi Hastuti (Jurnal Prajaiswara, 2026)
Introduction/Main Objectives: This study aims to analyze the development and impact of the School Participation Rate, Informal Sector, Child Workers’ Income, and the Number of Poor Population on the Number of Child Workers in the 10 provinces with the highest child labor rates in Indonesia during the period 2018–2024. Background Problems: Changes in national dynamics have influenced the development of the number of child workers in several regions of Indonesia, particularly in the 10 provinces with the highest number of child laborers. Research Methods: The study uses secondary panel data from 2018–2024 obtained from Statistics Indonesia (Badan Pusat Statistik), the Sakernas website, and the ILO (International Labour Organization). Finding/Results: The Informal Sector (SI) has a probability value of 0.0000 < 0.05, indicating a positive and significant effect, while the Number of Poor Population (JPM) has a probability value of 0.0096 < 0.05, indicating a negative and significant effect. Meanwhile, the School Participation Rate (APS) has a probability value of 0.8651 > 0.05, indicating a negative but not significant effect, and Child Workers’ Income (PPA) has a probability value of 0.6747 > 0.05, indicating a positive but not significant effect. Conclusion: The results of this study confirm that the number of child workers in Indonesia is more strongly influenced by the informal sector and the number of poor people than by the school participation rate and child workers’ income.